2006
DOI: 10.1159/000094422
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Legal Status, Perceived Pressure and Motivation in Treatment for Drug Dependence: Results from a European Study of Quasi-Compulsory Treatment

Abstract: This paper reports on intake data from Quasi-Compulsory Treatment in Europe, a study of quasi-compulsory treatment (QCT) for drug dependent offenders. It explores the link between formal legal coercion, perceived pressure to be in treatment and motivation amongst a sample of 845 people who entered treatment for drug dependence in five European countries, half of them in quasi-compulsory treatment and half ‘voluntarily’. Using both quantitative and qualitative data, it suggests that those who enter treatment un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 62 publications
2
24
0
4
Order By: Relevance
“…This result supports some of our previous results [49] in which no differences in retention were found. However, survival analyses on treatment retention yielded interesting differences in some baseline outcome predictors, which have to be further investigated.…”
Section: Discussionsupporting
confidence: 93%
“…This result supports some of our previous results [49] in which no differences in retention were found. However, survival analyses on treatment retention yielded interesting differences in some baseline outcome predictors, which have to be further investigated.…”
Section: Discussionsupporting
confidence: 93%
“…This created the perverse incentive that committing certain crimes was the most effective means of accessing treatment services. There is, however, little concrete evidence for this and other research has shown that the success of drug treatment or otherwise depends on the motivations of the offender, which, in turn, is contingent on factors such as whether legal pressure is applied to treatment, the length of the treatment episode, medical status, employment/support status, levels of drug/alcohol use, family and social relationships and psychiatric status (Stevens et al, 2006).…”
Section: New Labour's Early Drug Strategy and Policymentioning
confidence: 87%
“…For example, an American study in 3 inpatient therapeutic communities found that perceived legal pressure predicts better retention, while pressure from families predicts worse retention [24] . Stevens et al [25] suggested that participants entering QCT perceive more pressure, but this does not necessarily lead to higher or lower motivation than under voluntary treatment. They suggest that motivation is mutable and that it can be enhanced or diminished by the quality of support and services in QCT.…”
Section: Perceived Pressure and Coercionmentioning
confidence: 99%
“…Services from the United Kingdom, Italy, Austria, Germany, and Switzerland were selected if they treated participants eligible for either QCT or voluntary groups [4,25] . The QCT group was defined as participants receiving treatment on court order (i.e.…”
Section: Services and Participant Selectionmentioning
confidence: 99%